Design principles in commons science: A response to "Ostrom, Hardin and the commons" (Araral). Issue 61 (July 2016) - Cox, Michael; Villamayor-Tomas, Sergio; Arnold, Gwen
Highlights: We respond to a critique of our previous meta-analysis of Ostrom's design principles. We agree with elements of this critique, but argue against others. We also correct some factual errors contained in this critique. We believe this critique can be extended to Ostrom's work and the commons literature. Abstract: Within the literature on common-pool resource management, one of the primary methodologies used is the meta-analysis of case studies, due to the difficulties of otherwise producing large-n datasets that span multiple systems. In this paper we respond to a critique of a previous meta-analysis that we have conducted, in which we evaluated Elinor Ostrom's institutional design principles. Within our response we correct what we perceive to be factual errors contained in this critique, but more importantly we try to use this opportunity to re-evaluate our own work and expand this evaluation to the seminal work of Elinor Ostrom and the research program on common-pool resource management. We find that the original critique highlighted several important points, primarily the challenge of unpacking complex variable relationships and the conflation of diverse outcomes, and we discuss how these are challenges for the larger commons field. We conclude with some comments on how to move forward to confront these challenges.